Obstetric Care Performance: A Situational Analysis of 24×7 Primary Health Centres from Gujarat, India (Global Journal of Medical Research, 2015)
Primary Health Centers are the cornerstone of rural healthcare in India. Updating these centers to provide round the clock services to reduce the unmet need for maternal healthcare; is an important objective of National Rural Health Mission since 2005. Yet, functionality of PHCs to provide 24×7 services remains poor due to several health system issues. The present cross-sectional facility based study evaluates the functioning of rural 24×7 primary health care facilities in 3 districts of Gujarat for obstetric care performance and its predictors. The study used pretested questionnaire for collecting data from all PHCs of study areas in 2012-13. Obstetric care performance was measured as number of deliveries conducted in last 3 months. Current study found that the obstetric care performance is independent of infrastructure or logistics situation but highly dependent availability on the skilled human resource. There is urgent need for a systematic study to evaluate performance of public health facilities along with use of routinely collected data to make the system efficient.
Keywords: obstetric care performance; primary health centres; 24x7 PHCs